SUBALKALINE PICROBASALTS AND PLATEAU BASALTS FROM PUTORANA PLATEAU (SIBERIAN CFB PROVINCE). I. MINERAL COMPOSITIONS AND GEOCHEMISTRY OF MAJOR AND TRACE ELEMENTS - Ryabchikov I.D.; Ntaflos T.; Büchl A.; Solovova I.P. (My University, 2001)
In this article, we report on the results of the investigation of trace and major element contents and compositions of minerals for the representative collection of subalkaline picritic basalts from the Putorana plateau and for tholeiitic plateau basalts sampled from the same locality. Subalkaline picritic basalts (SAPB) are characterized by a significant enrichment in highly incompatible trace elements and steep LREE enriched rare earth element patterns, whereas tholeiitic flood basalts (TFB) show only a mild enrichment in incompatible elements and flatter REE patterns. High levels of incompatible elements in SAPB are reflected in the abundance of accessory apatite, baddeleyite, and altered zirconolite in them. Minerals of the armalcolite-pseudobrookite series are present in solidified melt inclusions in olivine phenocrysts. Olivine phenocrysts in SAPB contain crystalline inclusions of Ti-rich chrome spinel with a significant fraction of the magnetite component, which points to the high values of oxygen fugacities. Certain geochemical features of SAPB (high values of Ti/Na and Lu/La ratios, negative K and P anomalies on BSE normalized diagrams) show that their primary magmas formed at very high pressures. The TFB lack these high pressure characteristics, but are characterized by distinct Nb and Ta negative anomalies, which imply a certain level of crustal contamination, whereas, in MgO-rich SAPB, Nb and Ta anomalies are absent.